A proposed proficiency test in English for freshman college students - Tabor, Myrna G. (Andres) 1951- (s.n.], 1973)
A proficiency test in English covering the elements, phonology, lexicon and structure in second language situation is presented in this study. This test was designed for freshman college students of varying linguistic background.